Strategi Komunikasi Public Relations CJ CGV Cinemas dalam Mengenalkan Konsep Cultureplex di Masa Pandemi - Viany Adventa Widiarja; Davis Roganda Parlindungan (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
The COVID-19 pandemic has affected all aspects of life. Likewise with the CJ CGV Cinemas cinema, which experienced the same thing, therefore the researchers tried to examine the existing problems through the theory of communication strategy. Researchers want to know how the communication strategy implemented by CJ CGV Cinemas' public relations to maintain its existence during the current pandemic through its concept, namely culturelex. This study uses a descriptive approach and constructivism paradigm. Data collection was obtained through in-depth interviews, observation and documentation. In selecting research informants, the researcher used purposive sampling technique. The results of this study indicate that the public relations of CJ CGV Cinemas through its communication strategy to implement the cultureplex concept through official social media accounts, write press releases and hold media visits, conduct non-film activities such as social activities to become a place for elderly vaccines, present innovative new concepts. , and the last one presents alternative content.